Infant temperament as a predictor of maternal attachment: A Jordanian study - Abuhammad, Sawsan (Nurs Open, 2020)
AIM: To investigate the relationship between maternal bonding and infant temperament during the first year of infant's life. Moreover, it also wanted to explore which perinatal factors could influence the quality of maternal attachment. METHOD: A cross‐sectional study design was used to collect data from a sample of 277 mothers during the period of May–October 2018. The participants were asked to complete a three‐part survey that was developed to collect data on maternal attachment and infant temperament. Data was collected between March 2019–June 2019. RESULTS: The analysis of the data revealed that there was a significant relationship between infant temperament and maternal attachment [F(2, 95) = 6.783, p‐value = .001]. It also revealed that the factors that most influenced maternal attachment were infant temperament and planned pregnancy, which together explained 54% of the variance in maternal attachment (R (2 ) =  7.5). CONCLUSION: Maternal attachment in Jordanian mothers can be explained by two significant factors: infant temperament and planning for pregnancy.